The Mediating Role of Financial Well-Being in the Relationship between Financial Behavior and Stress Among Irregular Income Workers - Nurkhalida, Khairunisa; Renanita, Theda (Universitas Islam Indonesia, 2025)
Psychological well-being is characterized by low stress levels and influenced by financial factors. Therefore, this research aims to determine the effect of financial behavior on stress mediated by financial well-being. An instrument validation test was conducted with 200 participants, followed by a hypothesis model including 266 individuals aged 20–40 years with irregular income patterns. Monte Carlo simulations suggested that a sample of 200 was estimated to produce statistical power approaching 0.8 using a purposive non-probability method. Stress instrument, Financial Management Behavior Scale, and Financial Well-being Scale from DASS-21, Dew and Xiao (2011), and Prawitz (2006) were adopted, respectively. According to the hypothesis, financial well-being mediated the relationship between behavior and stress. Data analysis was performed using an efficient macro process in the statistical analysis process. The results showed that financial well-being had a full mediating role in the influence of financial behavior on stress. The primary contribution of this research lies in offering insights into stress reduction through the enhancement of financial well-being.